Sei \({ v \in \ker \psi \cap \varphi(U) }\) dann gibt es ein \({ u \in U }\) mit \({ \varphi(u) = v }\). Wegen \[ \psi(\varphi(u)) = \psi(v) = 0 \] liegt \({ u }\) in \({ \ker (\psi \circ \varphi) }\) und damit \[ v = \varphi(u) \in \varphi(\ker (\psi \circ \varphi)) . \] Also gilt \({ \ker \psi \cap \varphi(U) \subseteq \varphi(\ker (\psi \circ \varphi)) . }\)
Sei nun \({ v \in \varphi(\ker (\psi \circ \varphi)) \subseteq \varphi(U) }\) dann gibt es ein \({ u \in \ker (\psi \circ \varphi) }\) mit \({ v = \varphi(u) }\). Wegen \[ \psi(v) = \psi(\varphi(u)) = 0 \] liegt \({ v }\) in \({ \ker \psi }\). Daraus folgt \({ \ker \psi \cap \varphi(U) \supseteq \varphi(\ker (\psi \circ \varphi)) . }\)